Réponses

2014-10-04T18:02:35+02:00
-10x² - 6x + 4 = 0 => 5x² + 3x - 2 = 0 => x² +3/5x -2/5 = 0 
=> (x + y)² = x² + 2xy + y² mais 2xy = 3/5x => y = 3/10 
=> (x+ 3/10)² = x² + 3/5x + 9/100 => x² + 3/5x = (x+3/10)² - 9/100
donc x² +3/5x -2/5 = (x + 3/5)² - 9/100 - 2/5 = (x + 3/5)² - 49/100
=> x² +3/5x -2/5 = 0  = (x + 3/5)² - 49/100 = 0 => (x+3/5)² = 49/100
=> x + 3/5 = 7/10 => x = 1/10
ou x + 3/5 = -7/10 => x = -13/10
tu as compris?
Non je ne comprends rien... Au pire j'ai une expression équivalente, (5x+2)(2-2x) = 0, mais là aussi je bloque